Exploring job crafting behaviors among primary and secondary school teachers in China: a descriptive analysis - Zhang, Shiyu; Huang, Xianhan; Wang, Chan (Frontiers in Education, 2025)
The evolving landscape of educational reform, coupled with the unique nature of the teaching profession, has positioned job crafting as a promising strategy to enhance teachers’ ability to deliver knowledge, foster student development, and support their own professional growth. This study aims to investigate the job crafting behaviors and their influencing factors among primary and secondary school teachers. A total of 1,886 teachers from Yunnan and Gansu provinces in western China were randomly surveyed using a structured self-report questionnaire. The instrument included demographic items and a five-dimensional job crafting Likert-scale. Descriptive statistics, independent sample t-tests, one-way ANOVA, and correlation and regression analyses were conducted using SPSS. To ensure the construct validity of the job crafting scale, confirmatory factor analysis was performed using Mplus. The results yielded four main findings: (1) Gender did not significantly impact overall job crafting behaviors; however, male teachers reported higher scores in increasing social and challenging job resources compared to their female counterparts. (2) Both age and years of teaching experience significantly influenced teachers’ overall job crafting behaviors, with older teachers and those with more experience exhibiting higher job crafting scores. (3) Regarding teaching positions, school administrators reported higher levels of job crafting in increasing social job resources, increasing challenging job demands, and optimizing job demands. (4) Teachers from different types of schools showed significant differences in increasing structural job resources, with teachers from district-level schools scoring lower in this dimension.